(untitled) (Al-Aasar, 2025)
Background: Emotional intelligence (EI) refers to the skill of becoming aware of knowing and controlling emotions whether in oneself or in others. It has been attributed to academic performance, interpersonal effectiveness, stress management and professional competence in nursing. Learning about EI in nursing students can assist the teachers in creating methods that would enhance academic and clinical performance. Objective: To test the hypothesis on the relationship between emotional intelligence and academic success of nursing students in various institutions in Multan, Pakistan. Methods: A correlational study was performed as a descriptive study of 300 nursing students in BSc Nursing programs in various institutions in Multan. A validated Emotional Intelligence Scale (Schutte Self-Report Emotional Intelligence Test - SSEIT) and academic records (GPA) were used to collect the data. The demographics, EI and academic success were summarized using descriptive statistics. Pearson correlation was used to determine the relationship between EI and GPA, and regression analysis was used to determine predictive subcomponents. Results: The EI score had an average of 125.6 ± 15.2 (range: 90-160), empathy and self-regulation had the highest correlations with academic success. The mean GPA was 3.2 ± 0.4. There was a high positive relationship between EI and GPA (r = 0.48, p < 0.01). Regression analysis showed that EI predicted 22 percent of the academic performance (R2 = 0.22, p < 0.001) with self-regulation and empathy being the best predictors. Conclusion Academic success of nursing students is positively linked to emotional intelligence. To improve academic and professional competence, nursing educators need to incorporate EI development strategies, such as workshops, mentorship programs, and stress management programs.